Jurisdictional Ambiguity over Corruption Crimes Committed by Military Personnel under Indonesia’s New Criminal Law Framework - Agustinus Purnomo Hadi; Prastopo Prastopo; Maya Sri Novita; Ridwan Ridwan (State Islamic University of North Sumatra Indonesia, 2026)
The enactment of Indonesia’s National Criminal Code raises a new legal issue concerning the jurisdictional position of corruption crimes committed by military personnel. The problem lies in determining whether the competent court should be based on the offender’s military status or on the special nature of corruption crimes, which involve state financial losses, abuse of public authority, institutional integrity, and public trust. This study uses normative juridical research with statutory, conceptual, and institutional approaches. The analysis examines the relationship between the National Criminal Code, anti-corruption legislation, military justice law, and selected court decisions involving corruption crimes committed by military personnel. The study finds that judicial practice still relies on military courts and connected-case mechanisms in handling such cases. However, these mechanisms have not fully resolved the ambiguity between offender-status-based jurisdiction and offense-based jurisdiction. This article argues that jurisdiction should be determined through a functional approach by considering the offender’s status, the nature of the offense, the object of loss, the lex specialis principle, public accountability, and the institutional purpose of anti-corruption adjudication. Military courts should remain relevant for offenses directly related to military discipline and command, while corruption crimes that harm state finances and public integrity should retain their special character within the national criminal justice system.